Liposome-chitosan hydrogel bead delivery system for the encapsulation of linseed oil and quercetin: Preparation and in vitro characterization studies. (January 2020) - Huang, Juan; Wang, Qiang; Chu, Lanling; Xia, Qiang
Abstract: This study concentrates on developing linseed oil and quercetin co-loaded liposomes-chitosan hydrogel beads to enhance their stability and solubility. Scanning electron microscope (SEM) analysis revealed that the constructed hydrogel beads had three-dimensional network structure and liposomes were entrapped evenly within polymer network. X-ray diffraction (XRD) study illustrated that quercetin was in an amorphous or dissolved form in hydrogel beads. Thermodynamic properties of chitosan and soybean lecithin with phosphatidyl cholines of 60% (PC60) changed after ion crosslinking. After loaded into hydrogel beads, the release of quercetin and ɑ-linolenic acid became slow and can be explained by Higuchi model which indicated that bioactives were released from the skeleton of the hydrogel beads by the mechanism of Fick diffusion. The in vitro simulated digestion study showed that hydrogel beads could improve the stability of liposomes in gastrointestinal tract and inhibit the rapid release of fatty acids. The accelerated oxidation and photostability studies showed that the chemical stability of functional bioactives could be improved by loading liposomes into hydrogel beads. Hence, chitosan hydrogel bead is an attractive candidate for the encapsulation of functional bioactives for use in food industry. Highlights: Linseed oil and quercetin co-loaded hydrogel beads were fabricated. The constructed hydrogel beads had obvious three-dimensional network structure. The sustained release effect can be observed by loading liposomes into hydrogel beads. Hydrogel beads could improve the stability of liposomes in gastrointestinal tract. Chemical stability of bioactive was improved by loading liposome into hydrogel bead.